Examination of Differences in Using Marketing Tools in the Management of SMEs in the Visegrád Group Countries - Jaroslav Belas; Beata Gavurova; Lenka Novotna; Lubos Smrcka (Amfiteatru Economic)
The main aim of the study is to examine the differences in the use of the marketing tools in the management of small and medium-sized enterprises in the Visegrád Group (V4) countries. The research was carried out via questionnaires, which were distributed to small and medium-sized firmsin 2020. We obtained 1585 observations, which comprised the answers of business owners and managers. Binary logistic regression was used to process the data. Currently, firms rarely use the classic tools of the marketing mix. These tools are used to a minimal extent in construction and services. Proactive tools of the marketing mix are mostly used in transportation and retailing, and the least in manufacturing, construction, tourism, and other areas of business. Online marketing tools are mostly used in retailing, tourism, and services, and are less used in agriculture, construction, and transportation. The analysis results confirmed the differences in using the marketing mix tools depending on the age of the firm, the age of managers vs. entrepreneurs, and gender. The study results provide valuable information for creators of marketing conceptions, and for creators of regional and national development strategies. Similarly, these results encourage the creation of new marketing concepts and methodologies to evaluate their economic effects on firms and society